From flowers to seeds: how the metabolism of flowers frames plant reproduction. (4th June 2021) - Borghi, Monica; Fernie, Alisdair R.
Abstract : Flowers are characterized by a plenitude of primary and secondary metabolites and flower-specific biosynthetic pathways that all concur to promote plant reproduction and the initial stages of embryo development. The floral secondary metabolites of flowers contribute to scent and colour, which are used by flowers to attract pollinators. Besides, many metabolites responsible for the conferral of colour also serve as photo-protectants towards the damaging effects of UV solar radiation. The whole metabolism of flowers is sustained by a network of primary metabolites that provide metabolic precursors for the biosynthesis of secondary metabolites and support flower development. Moreover, many primary metabolites are channelled into nectar, the food of pollinators. However, this complex metabolic network is susceptible to environmental constraints such as heat and drought, which can hamper plant reproduction by destabilizing the whole metabolism of flowers. Here, we provide a short overview of the different metabolic pathways of flowers and how they support pollination and fertilization.